Rationalizations and Political Polarization - Yves Le Yaouanq; Peter Schwardmann; Joël J. van der Weele (CESifo GmbH, 2025)
We present a self- and social-signaling model formalizing findings in political psychology that moral and political judgments stem primarily from intuition and emotion, while reasoning serves to rationalize these intuitions to maintain an image of impartiality. In social interactions, agents' rationalizations are strategic complements: others' rationalizations weaken their ability to judge critically and make their actions less revealing of (inconvenient) truths. When agents are naive about their own rationalizations, our model predicts ideological and affective polarization, with each side assigning inappropriate motives to the other. Cross-partisan exchanges of narratives reduce polarization but are avoided by the agents. In within-group exchanges agents favor skilled speakers, whose narratives worsen polarization. Our model explains partisan disagreements over policy consequences, aligns with empirical polarization trends, and offers insights into efforts to disrupt echo chambers.
Keywords: D72; D83; D91; P16; 330; esteem; moral behavior; self-deception; group decisions; polarization